2017
DOI: 10.4028/www.scientific.net/ddf.374.18
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Asymmetrically Confined Circular Cylinder and Opposing Buoyancy on Fluid Flow and Heat Transfer

Abstract: In this paper, a two-dimensional numerical investigation is carried out to understand the effects of opposing thermal buoyancy and Prandtl number on fluid flow and mixed convection heat transfer characteristics of symmetrically and asymmetrically confined cylinder submerged in Newtonian fluid. The detailed flow and temperature field are illustrated in term of streamlines and isotherm contours to interpret the flow and thermal transport visualization. The numerical results are presented and discussed for the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 9 publications
4
28
0
Order By: Relevance
“…The accuracy of the numerical simulation is validated and presented in our earlier works [1] and [14] for Nusselt number dependence on Reynolds number for various Richardson number and Prandtl number.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy of the numerical simulation is validated and presented in our earlier works [1] and [14] for Nusselt number dependence on Reynolds number for various Richardson number and Prandtl number.…”
Section: Resultsmentioning
confidence: 99%
“…Very small size control volume near the surface is adopted with a total number of cells 120358 elements. The mesh sizes as well as the upstream and downstream distances are adopted after performing a comprehensive grid independency study which presented in our earlier works [1] and [14].…”
Section: Solution Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the heat transfer of fluids is related to a set of criteria mainly connected to the geometric shape of the system and the fluid quality (Maneengam et al 2022;Laidoudi and Bouzit 2018;Aliouane et al 2021;Selimefendigil 2019;Alsabery et al 2020;Gangawane et al 2018). Geometry has an effect on the fluid motion allowing for an effect on heat transfer (Laidoudi and Bouzit 2017;Herouz et al 2022;Anouar and Mokhefi 2022;Laidoudi, 2020). However, the quality of the fluid affects the thermal properties, which affects the heat capacity and thermal conductivity of the fluid (Abderrahmane et al 2023;Laidoudi and Ameur 2020;Mohebbi and Rashidi 2017;Usman et al 2019;Laidoudi and Ameur 2022).…”
Section: Introductionmentioning
confidence: 99%
“…All studies related to thermal activity aim to find possible solutions to accelerate heat transfer. A thermal system often consists of hot and cold elements immersed in a fluid such as air, water or some other type of fluid (Al-Kouz et al, 2021;Laidoudi, and Bouzit, 2017a;Hussain et al, 2019). It can be said that thermal systems are present in all industries and technology applications such as high-precision cooling systems, heat exchangers, nuclear stations, solar energy systems and other applications.…”
Section: Introductionmentioning
confidence: 99%